SUMO enhances vestigial function during wing morphogenesis. - Takanaka, Y.; Courey, A.J. (Mechanisms of Development, 2005)
The conjugation of the ubiquitin-like protein SUMO to lysine side chains plays widespread roles in the regulation of nuclear protein function. Since little information is available about the roles of SUMO in development, we have screened a collection of chromosomal deficiencies to identify developmental processes regulated by SUMO. We found that flies heterozygous for a deficiency uncovering vestigial (vg) and mutations in any of several genes encoding components of the SUMO conjugation machinery exhibit severe wing notching. This phenotype is due to an interaction between sumo and vg since it is suppressed by expression of Vg from a transgene, and is also observed in flies doubly heterozygous for vg hypomorphic alleles and sumo. In addition, the ability of Vg to direct the formation of ectopic wings when misexpressed in the eye field is enhanced by simultaneous misexpression of SUMO. In S2 cell transient transfection assays, overexpression of SUMO and the SUMO conjugating enzyme Ubc9, but not a catalytically inactive form of Ubc9, results in sumoylation of Vg and augments the activation of a Vg-responsive reporter. These findings are consistent with the idea that sumoylation stimulates Vg function during wing morphogenesis.